2006
DOI: 10.3171/spi.2006.4.6.447
|View full text |Cite
|
Sign up to set email alerts
|

Subsidence of the Wing titanium cage after anterior cervical interbody fusion: 2-year follow-up study

Abstract: Object Cage subsidence occurs after anterior cervical discectomy and fusion (ACDF). The aim of this prospective study was to evaluate subsidence and total segmental height after implantation of a newly designed Wing titanium cage. Furthermore, alignment of the entire cervical spine was analyzed 2 years after surgery. Methods Fifty-four patients (26 women and 28 men) whose mean age was 48.3 years underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 13 publications
5
124
0
1
Order By: Relevance
“…Gercek et al [10] reported that 5 of 8 patients (9 levels, 62.5%) had radiological signs of cage subsidence and recommended additional stabilization is necessary to avoid this problem though cage subsidence did not correlate with clinical symptoms. In a prospective study [22], subsidence was present in 30 of the 67 (44.8%) fused segments of ACDF using a titanium cage, but the height of the foramen was well maintained among the subsidence cases. The occurrence of local kyphosis was rare and did not cause any clinical complications after 2 years follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Gercek et al [10] reported that 5 of 8 patients (9 levels, 62.5%) had radiological signs of cage subsidence and recommended additional stabilization is necessary to avoid this problem though cage subsidence did not correlate with clinical symptoms. In a prospective study [22], subsidence was present in 30 of the 67 (44.8%) fused segments of ACDF using a titanium cage, but the height of the foramen was well maintained among the subsidence cases. The occurrence of local kyphosis was rare and did not cause any clinical complications after 2 years follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Cage subsidence is the most considered problem for stand-alone cage technology. Subsidence of titanium cages is observed in 13 to 45 % of cases in larger series [3,25]. The reported rate of PEEK cage subsidence varies from 8 to 15 % [13,35].…”
Section: Discussionmentioning
confidence: 96%
“…This phenomenon may occur due to insufficient fixation power of the cage alone. Indeed, some surgeons [5,7,8,14,15] have reported a significantly higher incidence of cage subsidence and subsequent local kyphosis in patients who received a cage alone compared to patients who received plate augmentation. Furthermore, fusion time was significantly delayed in these studies, and the fusion rate was significantly lower amongst patients who had the cage alone compared to those who had plate augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The cage can provide stability, high fusion rates and low subsidence [12][13][14][15]. There are many studies [5,6,12] on the favourable results of one-or twolevel anterior cervical fusion using a PEEK (polyetheretherketone) cage in degenerative cervical spine disease, including our previous report [5,12].…”
Section: Introductionmentioning
confidence: 92%